Penerapan Laravel untuk Mengatasi Kelemahan Keamanan WordPress pada Website Badan Layanan Umum Daerah - Sholeh, Muhammad; Iman Saputra, Tegar Satria; Suraya, Suraya (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
The BLUD.co.id website was previously developed using the Content Management System (CMS) WordPress, but it encountered security issues in the form of URL redirect attacks that directed users to untrusted sites. This study aims to redesign the information system using the Laravel framework to enhance security and flexibility. The system was developed locally by applying the Model-View-Controller (MVC) architectural pattern and a relational database structure designed independently. The research employed a Research and Development (R&D) approach through the stages of design, implementation, and security testing. Tests were conducted on several scenarios, including SQL Injection, Cross-Site Request Forgery (CSRF), and login bypass. The results indicate that the Laravel-based system was able to reduce the risk of attacks by 80–82% compared to WordPress, while also demonstrating greater stability when handling invalid inputs. These findings highlight that Laravel can provide a significant contribution to delivering a more secure digital information platform for government services, while also opening opportunities for further research to evaluate its application in similar organizational contexts.